2015
DOI: 10.1371/journal.pntd.0003959
|View full text |Cite
|
Sign up to set email alerts
|

Is PCR the Next Reference Standard for the Diagnosis of Schistosoma in Stool? A Comparison with Microscopy in Senegal and Kenya

Abstract: BackgroundThe current reference test for the detection of S. mansoni in endemic areas is stool microscopy based on one or more Kato-Katz stool smears. However, stool microscopy has several shortcomings that greatly affect the efficacy of current schistosomiasis control programs. A highly specific multiplex real-time polymerase chain reaction (PCR) targeting the Schistosoma internal transcriber-spacer-2 sequence (ITS2) was developed by our group a few years ago, but so far this PCR has been applied mostly on ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 40 publications
5
72
1
1
Order By: Relevance
“…The most likely explanation for the relatively poor performance of the T. trichiura PCR, as seen in several studies, seems to be the robustness of T. trichiura eggs, hampering optimal DNA isolation (Verweij & Stensvold, 2014). Further improvement of the DNA isolation steps is therefore important, because as long as not each of the target helminth species can be diagnosed by the highly sensitive DNA detection-based methodology in combination with a relatively simple-to-use uniform sample-processing procedure, complementary microscopy examination of stool samples will remain indispensable (Wiria et al 2013; Cimino et al 2015; Gordon et al 2015; Meurs et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The most likely explanation for the relatively poor performance of the T. trichiura PCR, as seen in several studies, seems to be the robustness of T. trichiura eggs, hampering optimal DNA isolation (Verweij & Stensvold, 2014). Further improvement of the DNA isolation steps is therefore important, because as long as not each of the target helminth species can be diagnosed by the highly sensitive DNA detection-based methodology in combination with a relatively simple-to-use uniform sample-processing procedure, complementary microscopy examination of stool samples will remain indispensable (Wiria et al 2013; Cimino et al 2015; Gordon et al 2015; Meurs et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Early warnings are di cult to provide as the maturation of schistosomes from schistosomula to adult worms takes > 28 days. Molecular assays may serve as potential alternatives to conventional sentinel mice dissection methods in situations where highly sensitive tests capable of gauging transmission risk in lowprevalence areas are needed [43]. Wang et al showed that the speci c antibodies IgM and IgG against Sj23HD in sentinel mice could be found at day 7 to 10 post-infection [44].…”
Section: Discussionmentioning
confidence: 99%
“…stercoralis [19,20]. The technique showed high sensitivity according to a large number of samples subjected to this platform between 2006 and 2012, comprising patient samples from the Netherlands and several African, Asian, and South American countries.…”
Section: Diagnosis Of Strongyloidiasismentioning
confidence: 99%